USULAN PENERAPAN TOTAL PRODUCTIVE MAINTENANCE (TPM) GUNA MENINGKATKAN KINERJA MESIN ELEKTROPLATING DI PERUSAHAAN FURNITUR TANGERANG - Didik Apriatno (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. PT. Utama Raya Motor Industry is a company engaged in the field offurniture have a problem relating with the frequency of downtime continues toincrease every time due to the damage caused to machinery. Therefore, thenecessary steps to be able to cope with and prevent such problems. TotalProductive Maintenance (TPM) is one method that can be used to improve theproductivity and efficiency of machinery effectively. One application of TPM is ameasure the Overall Equipment Effectiveness (OEE), then proceed with the sixbig losses OEE measurement to determine the efficiency of the missing and thelargest contributing factors that lead to low effectiveness of the six factors six biglosses. The data used from January to December 2014 with the object of researchelectroplating machine. During the month the average value obtained averagevalue results are low. From these measurements indicate that the setup andadjustment losses has donated the biggest losses in the engine electroplating,followed idling and minor stoppages losses. So that the necessary repairs heatingsystem solution and electroplating machine filter system to reduce losses thatoccur due to setup and adjustment losses and losses idling and minor stoppages.Keywords: TPM, OEE, six big losses, Pareto diagram, cause-effect diagram.